PENGARUH PENERAPAN WHISTLEBLOWING SYSTEM TERHADAP PENCEGAHAN FRAUD (Studi Empiris Pada Dinas Pendidikan Kabupaten Pasuruan) - ALIF FARUQI FEBRI YANTO (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2023)
This study aims to analyze empirical evidence of the effect of the whistleblowing system on the relationship between acts of fraud. Data collection was carried out by distributing questionnaires to Pasuruan Regency education office employees who had worked for more than 2 (two) years. Data analysis was carried out by simple linear regression analysis with the help of the SPSS 23 software program and the test results indicated that there was empirical evidence of the application of the whistleblowing system to the intensity of acts. This indicates that employees of the Pasuruan district education office who have high independence tend to pay attention to the existence of a whistleblowing system to prevent acts of fraud. Keywords: Whistleblowing system, fraud prevention